Hubungan antara grit dengan goal setting pada siswa kelas XII - Shofi Royani; Nawang Warsi Wulandari; Dellawaty Supraba (Jurnal Psikologi Tabularasa, 2022)
Completing education at school for class XII students is a transition to maturity to form the desired integrity, where at this time students are required to determine what goals they want. This study aims to determine the relationship between grit and goal setting in class XII students. The results showed that there was a positive relationship between grit and goal setting in class XII students. The correlation coefficient value obtained is 0.818 with a significant value of 0.000 (p <0.05). The higher the grit that students have, the higher the goal setting ability will be. The lower the grit that students have, the lower the goal setting ability will be. The population in this study were all class XII students in Lamongan Regency. The sampling technique used is the cluster random sampling technique. The research sample involved 111 class XII students in Lamongan Regency. The research method uses a correlational quantitative approach. The measuring instrument used is a grit scale and a goal setting scale.Menamatkan pendidikan di sekolah bagi siswa kelas XII merupakan suatu transisi menuju kedewasaan untuk membentuk integritas yang didambakannya, dimana pada masa ini siswa dituntut untuk menentukan goal apa yang dikehendakinya. Penelitian ini bertujuan untuk mengetahui hubungan antara grit dengan goal setting pada siswa kelas XII. Populasi dalam penelitian ini ialah seluruh siswa kelas XII di Kabupaten Lamongan. Teknik sampling yang digunakan yakni teknik cluster random sampling. Sampel penelitian melibatkan 111 siswa kelas XII di Kabupaten Lamongan. Metode penelitian menggunakan pendekatan kuantitatif korelasional. Alat ukur yang digunakan menggunakan skala grit dan skala goal setting. Hasil penelitian menunjukkan bahwasannya terdapat hubungan positif antara grit dengan goal setting pada siswa kelas XII. Nilai koefisien korelasi yang didapatkan sebesar 0,818 dengan nilai signifikan 0,000 (p<0,05). Semakin tinggi grit yang dimiliki siswa, maka akan semakin tinggi kemampuan goal setting. Semakin rendah grit yang dimiliki siswa, maka akan semakin rendah kemampuan goal setting.